2021
DOI: 10.1007/s10943-021-01357-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nurses' Death Anxiety on Life Satisfaction During the COVID-19 Pandemic in Turkey

Abstract: The purpose of the study is to determine the effect of nurses’ death anxiety on life satisfaction during the COVID-19 pandemic. This cross-sectional and correlational study was conducted with 411 nurses in Turkey. Data were collected online through Google Forms using a sociodemographic form, the Revised Death Anxiety Scale (RDAS), and the Satisfaction with Life Scale (SWLS). Percentages, means, Pearson’s correlation analysis, and hierarchical linear regression models were used to analyze the data. The nurses’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
(64 reference statements)
3
28
0
4
Order By: Relevance
“…The studies of Yiğit & Açıkgöz (2021) and Karabağ Aydın & Fidan (2021) also demonstrated that, during the COVID-19 pandemic, nurses had been exposed to significant levels of death anxiety. There was an indirect relationship between resilience and anxiety, which agrees with the present study's findings [ 31 , 32 ]. Likewise, Zukhra et al (2021) found that nursing students have experienced high anxiety and psychological stress levels during the current pandemic.…”
Section: Discussionsupporting
confidence: 93%
“…The studies of Yiğit & Açıkgöz (2021) and Karabağ Aydın & Fidan (2021) also demonstrated that, during the COVID-19 pandemic, nurses had been exposed to significant levels of death anxiety. There was an indirect relationship between resilience and anxiety, which agrees with the present study's findings [ 31 , 32 ]. Likewise, Zukhra et al (2021) found that nursing students have experienced high anxiety and psychological stress levels during the current pandemic.…”
Section: Discussionsupporting
confidence: 93%
“…At the beginning of the pandemic, there were many negativities, including uncertainties about the process, a high number of COVID-19 cases and mortality rates, demanding quarantine practices, the absence of a proven treatment for the disease, a high risk of transmission of the virus, lack of quality equipment, and the unpreparedness of healthcare systems and professionals to deal with the pandemic process. The fear and anxiety experienced by the nurses could be attributed to the feeling of isolation they have in bearing the brunt of responsibilities imposed on healthcare professionals, the self-awareness they have of being at the forefront of the battle against the pandemic, and the health risks that the pandemic poses to them and their families (Aydın & Hursit, 2021 ; Catania et al, 2021 ; Celik et al, 2020 ). Similar to the present study, other studies have reported that nurses may feel stress, anxiety, anger and disappointment due to lack of known treatments for the virus, their high risk of contamination, insufficient PPE and other required materials, and uncertainty about the future (Lau & Chan, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with pursuing important goals, whose attainment, or even the path to them, can be a source of satisfaction [ 22 , 23 ]. There are many literature reports on the evaluation of satisfaction with life, which results from a comparison of one’s own situation with one’s own standards [ 24 , 25 , 26 ]. It can be presumed that life satisfaction is one of the main predictors of loneliness, considering the variety of applied restrictions related to the COVID-19 pandemic and cultural conditions in different countries, as well as the assumptions of loneliness and life satisfaction theories [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Karabağ Aydın and Fidan showed in a Turkish study that a fear of death had a negative impact on satisfaction with life during the COVID-19 pandemic. A higher level of fear of death among nurses was associated with a lower level of satisfaction with life [ 26 ]. It was confirmed in another study that anxiety, mental health and social isolation were the main, statistically significant factors with an indirect impact on the quality of life of Turkish nurses [ 31 ].…”
Section: Introductionmentioning
confidence: 99%